The hidden crisis: COVID-19 and impact on mental health of medical students in Pakistan - Nazish Imran; Imran Ijaz Haider; Ali Burhan Mustafa; Irum Aamer; Zahid Kamal; Ghulam Rasool; Muhammad Waqar Azeem; Afzal Javed (Middle East Current Psychiatry, 2021)
Abstract Background Medical students have faced an enormous disruption to their lives due to the COVID-19 pandemic. The study aimed to assess the impact of COVID-19 on medical student’s psychological well-being in Pakistan. Following ethical approval, an online survey developed in collaboration with World Psychiatric Association (WPA) was distributed among medical students of 5 Medical colleges in the Punjab province of Pakistan between August and September 2020. Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder Scale (GAD-7), and Risk Assessment Suicidality Scale (RASS) were used to assess psychological well-being. Data was analyzed using SPSS 26.0. Results Eleven hundred medical students responded, 756 (69%) being females. More than 2/3rd admitted that their emotional state got worse in relation to appearance of anxiety, insecurity, and sadness, compared to before the outbreak of COVID-19. Prevalence of anxiety and depressive symptoms were 48.6% and 48.1%, respectively. Female medical students, pre-clinical students, and those with a previous psychiatric history reported experiencing more anxiety and depression symptoms (P value < 0.001). One in five medical students thought that it would be better if they were dead, and 8% admitted to often think of committing suicide during the past 2 weeks. RASS and subscales (intention, life, and history) scores were higher in females and students with previous psychiatric problems. Conclusion Our findings underscore that the impact of COVID-19 on medical students has been significant; hence, it is crucial for medical colleges to employ strategies to maintain the student’s well-being with safeguards like reassurance, support, and confidential student-centered psychiatric services. The use of virtual platforms (websites, email) to educate and screen students by staff members can create a positive impact. The limitations of this study include cross-sectional design, the possibility of selective participation being web-based survey, response bias, and the possibility of reluctance of students to report mental health problems due to stigma.